Representation of shape mediated by environmental stimuli in Physarum polycephalum and a multi-agent model. Issue 2 (4th March 2017) - Jones, Jeff; Mayne, Richard; Adamatzky, Andrew
Abstract : The slime mould Physarum polycephalum is known to construct protoplasmic transport networks which approximate proximity graphs by foraging for nutrients during its plasmodial life cycle stage. In these networks, nodes are represented by nutrients and edges are represented by protoplasmic tubes. These networks have been shown to be efficient in terms of length and resilience of the overall network to random damage. However, relatively little research has been performed in the potential for Physarum transport networks to approximate the overall shape of a data-set. In this paper we distinguish between connectivity and shape of a planar point data-set and demonstrate, using scoping experiments with plasmodia of P. polycephalum and a multi-agent model of the organism, how we can generate representations of the external and internal shapes of a set of points. As with proximity graphs formed by P. polycephalum, the behaviour of the plasmodium (real and model) is mediated by environmental stimuli. We further explore potential morphological computation approaches with the multi-agent model, presenting methods which approximate the Convex Hull and the Concave Hull. We demonstrate how a growth parameter in the model can be used to transition between Convex and Concave Hulls. These results suggest novel mechanisms of morphological computation mediated by environmental stimuli.